Mészáros: o tripé trabalho capital estado e suas implicações na educação - Celeste Deográcias de Souza Bitencourt (2016)
The thesis presents the result of our reading and immanent analysis of Beyond Capital: Toward a Theory of Transition, the main work of Mészáros (2002). It aims at apprehending the categories Work, Capital and State, at evidencing its implications on Education and at identifying how Mészáros treat these categories. The main guide elected to reach these objectives is a procedure based on a reading and immanent analysis of our object. Through this procedure, we seek to capture the genesis and the social telos of the analyzed object, i.e., its historical dimension, comprehending more profoundly the conception adopted by Mészáros to discuss these categories, nominated the tripod. The complex dialectical interrelations of the tripod complement, sustain and modify themselves, shaping the ongoing order. Firstly, we studied the whole books of Mészáros, aiming at identifying in which works the author directly discuss the cited categories, in order to define the corpus of the research. As a result of the procedure adopted, we conclude that the Mészáross theoretical approach to the historical synthesis of these categories enable us the proper understanding of the current historical epoch. Mészáros analyses the historical anachronism of the capital system, which, in its global, systemic and structural crises, activates its absolute structural limits and points towards the necessity and possibility of overcoming this order. According to the author, this would be possible only through the force of its hegemonic antagonist, the work. We seek to apprehend the conception of Education adopted by Mészáros and his comprehension of the implications of the tripod on the Education, considering that it is not the unique, nor the main, but is a fundamental component of the process of social transformation. Guided by the Marxian ontological matrix, Mészáros develop his own analyses of the work of Marx, exposing an ontology singularly humane through the work. Mészáros recover the revolutionary character of the Marxs social theory, which, in its originality, addresses the human emancipation, through the positive transcendence of the alienation of work, the eradication of capital and the withering of the State, a genuine Marxian project and a huge challenge to be achieved.